The Use of Storytelling Method in Teaching English with Islamic Content (Case Study of Modern Islamic Boarding School): Penelitian - Mella Erdianti; Silva Maysarah; Kariri Anwar; Roisul Umam Arrasyidi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to explore the effectiveness of the storytelling method in teaching English based on Islamic content in modern Islamic boarding schools. The background of this study is the need to integrate foreign language education with the instillation of Islamic values ​​without eliminating the identity of Islamic boarding schools as Islamic educational institutions. This study uses a qualitative case study approach with observation, interview, and documentation techniques as data collection methods. The results of the study indicate that the storytelling method not only improves students' communicative language skills but also functions as a means of conveying Islamic values ​​in a subtle, contextual, and non-boring manner. Islamic-themed stories delivered in English are able to foster interest in learning, shape character, and deepen students' religious understanding. In addition, this method is considered relevant to today's learning needs because it supports a humanistic and contextual approach. In conclusion, storytelling is an effective and flexible method for combining language learning with internalization of Islamic values ​​in a modern and enjoyable learning atmosphere.